RANCANGAN BUKU KERJA PENGUATAN PENGETAHUAN PEDAGOGI BAGI GURU BIOLOGI SMA - Andriani, Risa; Suryawati, Evi; Natalina L, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to know the quality of workbook pedagodical knowledge streghthening for senior high school biology teachers. The research procedures are: Analyze, Design, and Development. The workbook was developed based on essential indicator of Teacher Competency Test 2015. The phase of analysis, designing, developing, internal validation and first simulation were conducted in the Study Program of Biology Education FKIP University of Riau. External validation and second simulation were conducted in Biology MGMP Pekanbaru. Workbooks validated on four aspects include format; illustrations; language, and content. The result validation of pedagogical knowledge streghthening workbook has very valid category with score 3,38. The response in first simulation is 3.19 which is categorized good and the response in second simulation is 3.29 which is categorized very good. So, the pedagogical knowledge streghthening workbook can be used by teachers as one of the independent learning resources for prepare to follow Teacher Competency Test.Keywords: Workbook, pedagogical knowledge, high school biology teacher